Power flow analysis of DC distribution system in a ship with non-electric propulsion - Akhmad Reinaldy Kurniawan; Adi Kurniawan; Sardono Sarwito; Ahlur Roi Novanto Gumilang; Firman Budianto (Institute of Advanced Engineering and Science, 2023)
Direct current (DC) shipboard power distribution system offers higher power efficiency and voltage stability compared to the alternating current (AC) systems due to lower impedance. The implementation of DC distribution system in all-electric ship seems to be worthy since the reduction of power loss and voltage drop could overcome the drawback of DC system. However, the effectiveness of DC distribution system in ship with non-electric propulsion has not been investigated yet. Unlike in an all-electric ship, electric power flow in the distribution system of a ship with mechanic propulsion is considerably lower. The study aims to provide numerical analysis of power loss and voltage drop reduction on DC distribution system that applied to a ship with mechanic propulsion. The power flow analysis is performed on a tanker ship. Contrary to the hypothesis, the results show that the DC power distribution increase the power losses about 15% compared to AC system due to the addition of rectifier and inverter. However, the voltage drops are decreased in DC distribution system. Further investigation in the other aspects should be performed before concludes whether DC distribution system is worthy to be used in the aforementioned ship.